1965
DOI: 10.1017/s0003356100022303
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and heritability of fertility in hill sheep

Abstract: SUMMARYLambing records of 3,500 Scottish Blackface ewes and 2,000 Welsh Mountain ewes were used for a study of repeatability of ewe fertility and litter size. The repeatability of litter size at birth (calculated as an intra-ewe correlation) was higher in both flocks (0.19 and 0.24 for Blackface and Welsh ewes respectively) than that for barrenness (0.09 and 0.08) or for number of lambs born per mating (0.07 and 0.10). Repeatability of the corresponding traits at weaning were generally about half these values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
2

Year Published

1973
1973
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 5 publications
(5 reference statements)
6
11
2
Order By: Relevance
“…For example, an increase of 8 more lambs per 100 ewes joined per lQlb (4.5 kg) increase in body weight at 15-16 months of age was reported by Lax & Brown (1968), which is similar to the relationship with pre-mating weights found by Coop & Clark (1966). Coop & Hayman (1962) give values of between 4.6 and 8.2% twins born per 4.5 kg live-weight increase in ewes; and Purser (1965) quotes corresponding values of 7.1 and 13.3% for Blackface and Welsh sheep respectively. Cockrem (1965) has suggested a possible breakdown of the underlying relationships between fertility and live weight.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, an increase of 8 more lambs per 100 ewes joined per lQlb (4.5 kg) increase in body weight at 15-16 months of age was reported by Lax & Brown (1968), which is similar to the relationship with pre-mating weights found by Coop & Clark (1966). Coop & Hayman (1962) give values of between 4.6 and 8.2% twins born per 4.5 kg live-weight increase in ewes; and Purser (1965) quotes corresponding values of 7.1 and 13.3% for Blackface and Welsh sheep respectively. Cockrem (1965) has suggested a possible breakdown of the underlying relationships between fertility and live weight.…”
Section: Discussionsupporting
confidence: 72%
“…Many workers (Terrill & Stoehr 1942;Coop & Hayman 1962;Young et al 1963;Purser 1965;Lax & Brown 1968;Kennedy & Kennedy 1968;Edey 1970) have found that live weight and number of lambs weaned are positively associated. For example, an increase of 8 more lambs per 100 ewes joined per lQlb (4.5 kg) increase in body weight at 15-16 months of age was reported by Lax & Brown (1968), which is similar to the relationship with pre-mating weights found by Coop & Clark (1966).…”
Section: Discussionmentioning
confidence: 99%
“…The estimates of repeatability of NL W found in this study are not dissimilar to those reported by Young et al (1963), Purser (1965), Inskeep et al (1967), and Kennedy (1967) although the range of 0.12-0.25 published by Rae & Ch'ang (1955) is higher than that in Table 2.…”
Section: Number Of Lambs Weanedcontrasting
confidence: 50%
“…Also, measures of prolificacy based on number weaned can be seriously affected by pre-weaning losses and other traits such as ewe liveweight (Young et al 1963;Pursar 1965) and time of mating (Reeve and Robertson 1953;Bowman 1966). It has been assumed that, initially, the heritability of litter size at first lambing will be very low so selection should be based on the results of the third lambing rather than the first or pooled values for the first three.…”
Section: Planned Breeding and Selection For The Joint Jco Ieee Breedimentioning
confidence: 99%